Histories of the modern Middle East : new directions - Gershoni, Israel 1946-; Erdem, Hakan; Wokoeck, Ursula (Lynne Rienner, 2002)
Machine generated contents note: 1 Doing History: Modem Middle Eastern Studies Today, -- Israel Gershoni and Ursula Wokick -- Part 1 New Dimensions of Modernizing Processes -- 2 The Great Ottoman Debasement, 1808-1844: A Political Economy Framework, fevket Pamuk -- 3 A Prelude to Ottoman Reform: Ibn 'Abidin on Custom and Legal Change, Wael B. Hallaq -- 4 The Damascus Affair and the Beginnings of France's Empire in the Middle East, Mary C. Wilson -- 5 The Gender of Modernity: Reflections from Iranian Historiography, Afsaneh Najmabadi -- Part 2 Globalization Then and Now -- 6 From Liberalism to Liberal Imperialism: Lord Cromer and the First Wave of Globalization in Egypt, Roger Owen -- 7 Late Capitalism and the Reformation of the Working Classes in the Middle East, Joel Beinin -- Part 3 Recovering Lost Voices in the Age of Colonialism -- 8 Exploring the Field: Lost Voices and Emerging Practices in Egypt, 1882-1914, Zachary Lockman -- 9 Slaves or Siblings? Abdallah al-Nadim's Dialogues -- About the Family, Eve M. Troutt Powell -- 10 Shaikh al-Ra'is and Sultan Abdiilhamid II: The Iranian Dimension of Pan-Islam, Juan R. I. Cole -- Part 4 Constructing Identities, Defining Nations -- 11 Recruitment for the "Victorious Soldiers of Muhammad" in the Arab Provinces, 1826-1828, Hakan Erdem -- 12 The Politics of History and Memory: A Multidimensional Analysis of the Lausanne Peace Conference, 1922-1923, -- Fatma Miige Godek -- 13 Arab Society in Mandatory Palestine: The Half-Full Glass? -- Rashid Khalidi -- 14 Manly Men on a National Stage (and the Women Who Make Them Stars), Walter Armbrust